DIFFERENCE OF TOTAL CHOLESTEROL LEVELS BASED ON THE CENTRAL OBESITY AND FRUIT VEGETABLE CONSUMPTION PATTERNS GIANYAR DISTRICT - Ni Luh Made Tangkas Putri Hapsari; I Made Rodja Suantara; Hertog Nursanyoto (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Increased cholesterol levels in the blood is one of the risks of central obesity which can be caused by genetic factors, diet, and physical activity. The purpose of this study was to determine differences in total cholesterol levels based on the incidence of central obesity and consumption patterns of vegetables in Guwang Village, Sukawati District, Gianyar Regency. This type of research was observational with a crossectional design in 63 samples of men and women aged 21–60 years determined based on inclusion criteria and their proportional random sampling. The test data used was independent t-test. The results of the analysis showed (p0.05) there were differences in total cholesterol levels based on central obesity events, there were differences in total cholesterol levels based on vegetable consumption type (p0.05), there were differences in total cholesterol levels based on fruit consumption type (p0.05), there were no differences in total cholesterol levels based on the amount of vegetable and fruit consumption (p0.05), there were no differences in total cholesterol levels based on the frequency of vegetable consumption (p0.05), there were differences in total cholesterol levels based on frequency of consumption fruit (p0.05).Keywords: total cholesterol levels, central obesity, comsumption pattern of vegetables and fruit